Kenaikan Suhu Perairan Mengakibatkan Mastigias papua Menghilang Di Danau Laut Lenmakana Misool Kabupaten Raja Ampat, Papua Barat - Gandi YS Purba (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
Mastigias papua is a jellyfish that is trademark of marine lakes. Ongeim’l Tketau Lake in Palau, Hang Du I Lake in Vietnam, Kakaban Lake in Kalimantan, and Lenmakana Lake in Raja Ampat Papua are exotic tourist destinations because of presence of these biota in the lake. Water temperature is very influential on the life of a jellyfish because of its mutual symbiosis with brown algae zooxanthellae. Mastigias has totally disappeared in several places due to water temperature increasing, including Lenmakana Lake in the West Monsoon 2017/2018 and 2018/2019. The absence of Mastigias in this lake will be explained by recorded logger data installed in the lake and at sea. Secondary data from NOAA and BMKG will be used to explain the condition of absence of jellyfish. Water lake temperature data showed an increase to 2.5oC when the Mastigias disappeared. Temperature increasing occur due to seasonal cycle patterns of lake water temperatures and weather cycles which change in time, the dry season occurs faster and the rainy season occurs slower. Conversely, in the West Monsoon 2019/2020, Mastigias still found in the lake. The rainy season which is 20 days faster than normal condition helps reduce the heat in West Monsoon.